Downregulation of Long Noncoding RNA LINC00261 Attenuates Myocardial Infarction through the miR-522-3p/Trinucleotide Repeat-Containing Gene 6a (TNRC6A) Axis - Chaoxin Jiang; Qing Zhao; Chenlong Wang; Minyan Peng; Guoqing Hao; Zhifeng Liu; Wenjin Fu; Kewei Zhao (Cardiovascular Therapeutics)
Background. Myocardial infarction (MI) is cardiac tissue necrosis caused by acute and persistent ischemic hypoxia of the coronary arteries. This study is aimed at investigating the expression of long noncoding RNA (lncRNA) LINC00261 in MI and its effect on myocardial cells. Methods. qRT-PCR was performed to detect the expression levels of LINC00261, miR-522-3p, and TNRC6A in normal and MI cells. Western blotting analysis was performed to detect the expression of TNRC6A protein. Viability and apoptosis of myocardial cells after MI with the knockout of LINC00261 or TNRC6A were detected. The relationships among miR-522-3p, LINC00261, and TNRC6A in cardiomyocytes were evaluated using a double luciferase reporter gene assay. Hypoxic preconditioning in normal cells was used to construct a simulated MI environment to investigate the effect of LINC00261 on apoptosis of cardiac cells. Results. LINC00261 and TNRC6A were upregulated, while miR-522-3p was downregulated in coronary heart disease tissues with MI. Knockout of LINC00261 can increase the viability of cardiomyocytes and inhibit cell apoptosis. LINC00261 targets miR-522-3p in cardiomyocytes. In addition, miR-522-3p targets TNRC6A in cardiomyocytes. TNRC6A regulates cell viability and apoptosis of cardiomyocytes after MI, and TNRC6A-induced MI can be reversed by overexpression of miR-522-3p. Conclusions. LINC00261 downregulated miR-522-3p in cardiomyocytes after MI by directly targeting miR-522-3p. TNRC6A is the direct target of miR-522-3p. Our results indicated that LINC00261 might serve as a therapeutic target for the treatment of MI.